A qualitative examination of drinking patterns among community college students. Issue 2 (17th February 2021) - Thind, Herpreet; Rosen, Rochelle K.; Barnett, Nancy P.; Walaska, Kristen; Traficante, Regina; Bock, Beth C.
Abstract: Objective: The purpose of this study was to gain insight about patterns of alcohol use and related consequences among heavy drinking community college students. Participants: About 26 community college students (Mean age 22.3 years, 46% men, 69% White) participated in this study between January and April 2013. Methods: Five qualitative focus group discussions were conducted during formative research preceding a text message intervention; participants were asked about common drinking behavior patterns among community college students, as well as how age and gender affect drinking. Sessions were audio-recorded and transcribed verbatim. Participants also completed a brief quantitative survey about their drinking behavior and its consequences. Results: Qualitative data identified several themes: (1) reasons for drinking, (2) drinking occasions, (3) age- and experience-related differences in drinking, including patterns specific to community college students and women. Conclusion: Research is needed to develop innovative strategies to reduce alcohol harm in this understudied population.